Investigative Study of the Properties of Low Solid Drilling Fluid Prepared by Using Iraqi Bentonite - Assi, Amel H. (Journal of Petroleum Research and Studies, 2024)
This study aims to investigate the properties of drilling fluids with low solids content prepared using Iraqi bentonite. Polyacrylamide polymer, sodium polyacrylate polymer, Nano silica, and fine silica were used, as the results demonstrated the success of these materials in preparing drilling fluids with low solids content. As for micro silica, it is a material used with cement, but it was used in this study with drilling fluids because it is cheap in addition to being an environmentally friendly material. Polyacrylamide is a highly absorbent and effective material, which is usually used during well injection, but in this study it was used to improve the properties of Iraqi bentonite. 10 samples of drilling mud were prepared using the aforementioned materials in different proportions, and Iraqi bentonite was also used as a dispersant or dispersant phase. The percentage of bentonite during preparation ranged between (1.5-5) % in order to achieve sufficient gel resistance and balance the filtration speed. By drawing the relationship between shear stress and shear rate, it was found that all prepared samples follow the power law model, as this was used in hydraulic calculations in order to determine the pressure loss in the hydraulic system of the well. The results show that polyacrylamide polymer has the best effect on Iraqi bentonite among the other used materials in this study, where 1% from this material is enough to enhance properties (rheology and filtration) of Iraq bentonite. However, it has been observed from the laboratory results that when the percentage of bentonite is reduced to 1.5%, the prepared liquid will fail to suspend the barite and therefore will not achieve the required density in spite of the addition of barite. The best sample for the drilling fluid is when the percentage of the total solid is 5%, i.e. (10 gm Iraqi bentonite, 7 gm barite, 1 gm polymeric, Nano, or nanomaterials). As this drilling fluid had the best performance in terms of pressure loss, as they gave the least pressure loss.